1966
DOI: 10.1620/tjem.88.289
|View full text |Cite
|
Sign up to set email alerts
|

Two Types of Light Sleep and Central Visual Function in Cats

Abstract: Using cats carrying permanent electrodes, the central visual function was studied during the three phases of natural sleep (LS1, LS2, and DS). LS, and LS2 are the phases of light sleep (high-voltage slow wave sleep); LS1 is characterized by spindle activity and occasional desynchronized activity of the sensorimotor cortical EEG, whereas during LS2 slow waves are predominant. DS corresponds to so-called deep sleep (low-voltage fast wave sleep).1. Sensorimotor cortical and hippocampal electrographic signs of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1968
1968
1978
1978

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…The facilitation associated with the negative phase makes a great contribution to enhance the average discharge rate of the P units during deep sleep . This is also correlated with the previous finding by IWAMA and his associates that synaptic transmission at the LGB , seen at the level of mass activity, is temporarily facilitated in the presence of the DSWs (The observations of these workers were made without a distinction of the positive and negative phases of the DSWs)2e, 21,25,33). The evidence in the same line has been presented that the cellular component of the antidromic mass response of the LGB increases in amplitude while the DSWs are showing negative deflections19) .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The facilitation associated with the negative phase makes a great contribution to enhance the average discharge rate of the P units during deep sleep . This is also correlated with the previous finding by IWAMA and his associates that synaptic transmission at the LGB , seen at the level of mass activity, is temporarily facilitated in the presence of the DSWs (The observations of these workers were made without a distinction of the positive and negative phases of the DSWs)2e, 21,25,33). The evidence in the same line has been presented that the cellular component of the antidromic mass response of the LGB increases in amplitude while the DSWs are showing negative deflections19) .…”
Section: Discussionsupporting
confidence: 89%
“…They also noted that during deep sleep the transmission at the LGB suffers a transient facilitation when the otherwise desynchronized background activity yields the spiky waves20, 21,25,33) which have been called "deep sleep waves" (DSWs) by BROOKS and BIZZI8),"phasic activities" by M. JouvE24) or "LGB spikes" by MIKITEN et al 27) That modification of synaptic transmission of the LGB during sleep and wakefulness is not limited to the postsynaptic level but also extended to the presynaptic terminals of the optic tract fibers has been wellestablished20,25). It was shown that the presynaptic inhibition is developed most strongly during deep sleep and decreases from arousal to light sleep.…”
mentioning
confidence: 99%